Myopic Traction Maculopathy: Diagnostic and Management Strategies - Frisina R (Dove Medical Press, 2020)
Rino Frisina,1 Irene Gius,1 Michele Palmieri,2 Alessandro Finzi,3 Luigi Tozzi,1 Barbara Parolini2 1Department of Ophthalmology of University of Padova, Padova, Italy; 2Eyecare Clinic, Brescia, Italy; 3Villa Erbosa Di Bologna, Bologna, Emilia-Romagna, ItalyCorrespondence: Rino FrisinaDepartment of Ophthalmology of University of Padova, Via Giustiniani n. 2, Padova 35128, ItalyTel +39 0498212110Fax +39 049 8755169Email frisinarino@gmail.comAbstract: Pathologic myopia (PM) is an ocular disorder characterized by a spherical equivalent (SE) of more than – 6.0 diopters (D) or by an axial length (AL) of more than 26.5 millimeters (mm). PM is associated with myopic maculopathy (MM). The ATN classification describes all the aspects of MM which regroups atrophic, tractional and neovascular consequences to the sclera, choroid and retina of highly myopic eyes. The advent of OCT allowed to define the ultrastructural characteristics of the tractional changes in MM, described by the term myopic traction maculopathy (MTM). They include foveoschisis/maculoschisis/retinoschisis (FS/MS/RS), retinal/foveal detachment (RD/FD), lamellar macular holes (LMH) and full-thickness macular holes (FTMH) with or without RD (MHRD). The MTM staging system (MSS) describes all foveal and retinal changes related to MTM and their natural history interpreting them as different stages of a single progressive disorder. The management of MTM can be just observation for the earliest cases with good vision or surgery for the severe stages with vision loss. There are two possible surgical approaches: ab externo, that acts on the alteration of the scleral shape and includes posterior scleral reinforcement and macular buckle. Ab interno, that targets the alteration of the foveal profile and consists in pars plana vitrectomy with removal of all the epiretinal tractions, maneuvers on the internal limiting membrane, and the use of intravitreal tamponade and laser. As they target two different sides of the same pathology, the two techniques have to be selected on the base of the MTM stage, single or combined.Keywords: pathological myopia, posterior staphyloma, retinal detachment, full thickness macular hole, macular buckle, pars plana vitrectomy, myopic traction maculopathy